Analisis Pola Triadik Trinitarian dalam Perspektif Teologi Kovenan: Eksposisi Yohanes 14:26 - Adi, Didit Yuliantono; Purwonugroho, Daniel Pesah (Sekolah Tinggi Agama Kristen Diaspora, 2025)
The purpose of this paper is to analyze the trinitarian triadic pattern in the perspective of covenant theology with the exposition of John 14:26. The concept of the trinity is the foundation of Christian faith that affirms who and how God is. The trinitarian triadic pattern is seen in John 14:26 where the Father sends the Holy Spirit in the name of Jesus Christ. This pattern emphasizes the intra-trinitarian relationship involved in the lives of human beings. The trinitarian triadic pattern in John 14:26 can also be seen from the perspective of covenant theology. The presence of the Holy Spirit is the fulfillment of the covenant that the Father has established through the work of the Son from eternity. The fulfillment of the covenant has an active impact in the lives of believers. Through a descriptive qualitative approach, the author analyzes the triadic pattern of the trinity in the perspective of covenant theology through the exposition of John 14:26. The author states that the exposition of John 14:26 shows a trinitarian triadic pattern that is also closely related in the perspective of the covenant. This paper provides new theological insights in trinitarian studies through a covenantal approach.AbstrakTujuan dari tulisan ini adalah untuk menganalisa pola triadik trinitarian dalam perspektif teologi kovenan dengan eksposisi Yohanes 14:26. Konsep trinitas merupakan dasar iman Kristen yang menegaskan siapa dan bagaimana Allah itu. Pola triadik trinitarian terlihat di dalam Yohanes 14:26 dimana Bapa mengirimkan Roh Kudus dalam nama Yesus Kristus. Pola ini menegaskan hubungan intra-trinitarian yang terlibat di dalam kehidupan umat manusia. Pola triadik trinitarian dalam Yohanes 14:26 juga dapat dilihat dari perspektif teologi kovenan. Kehadiran Roh Kudus merupakan pemenuhan kovenan yang telah Bapa rangkai melalui pekerjaan sang Anak dari kekekalan. Pemenuhan kovenan tersebut berdampak aktif di dalam kehidupan umat percaya. Melalui pendekatan kualitatif deskriptif, penulis menganalisa pola triadik trinitaraian dalam perspektif teologi kovenan melalui eksposisi Yohanes 14:26. Penulis menyatakan bahwa eksposisi Yohanes 14:26 menunjukkan sebuah pola triadik trinitarian yang juga berkaitan erat dalam perspektif kovenan. Tulisan ini memberikan wawasan teologis yang baru dalam kajian trinitarian melalui pendekatan kovenantal.